2020
DOI: 10.1101/2020.05.12.092296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Genomic Landscape of Prostate Cancer Brain Metastases

Abstract: Lethal prostate cancer commonly metastasizes to bone, lymph nodes, and visceral organs but with more effective therapies, there is an increased frequency of metastases to the brain.Little is known about the genomic drivers of prostate cancer brain metastases (PCBM). To address this, we conducted a comprehensive multi-regional, genomic, and targeted transcriptomic analysis of PCBM from 28 patients. We compared whole-exome and targeted RNA sequencing with matched primary tumors when available (n = 10) and with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…Therefore, it is unclear whether our patient's dMMR status contributed to his development of brain metastases. Of note, this patient's brain metastases also exhibited alterations in PTEN as well as NF1, which may support prior work suggesting a correlation between PTEN and NF1 inactivation and brain metastases in prostate cancer (Mota et al 2019;Rodriguez et al 2020).…”
Section: )supporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, it is unclear whether our patient's dMMR status contributed to his development of brain metastases. Of note, this patient's brain metastases also exhibited alterations in PTEN as well as NF1, which may support prior work suggesting a correlation between PTEN and NF1 inactivation and brain metastases in prostate cancer (Mota et al 2019;Rodriguez et al 2020).…”
Section: )supporting
confidence: 86%
“…Given the rarity of prostate cancer with brain metastases, little is known about its molecular characteristics and its interaction with the immune microenvironment. Initial studies suggested that PTEN loss and DNA homologous repair (HR) mutations may be common in this entity (Mota et al 2019;Rodriguez et al 2020), however relatively few tumors have undergone DNA sequencing to date. Moreover, the immune cell composition of brain metastases from prostate cancer has not previously been described.…”
Section: Introductionmentioning
confidence: 99%
“…Dural metastases thus represent a late manifestation of disease across all cancer subtypes and are more frequently seen in those treated with a number of lines of therapy 8. Additionally, emerging data suggests BRCA mutated cancers including prostate cancers are more likely to develop central nervous system metastases 10…”
Section: Discussionmentioning
confidence: 99%